Sistem Pendeteksi Kualitas Air Di Sekitar Pesisir Pantai Tondo Menggunakan Metode Fuzzy Logic - Rusdin, Andi; Jumiyatun, Jumiyatun; Sesenggi, Moh Idham; Jayadi, Harsano (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
The disaster that hit Palu City recently caused changes in the quality of water consumed by the community. To find out whether it is feasible or not, we need a method to detect a water quality system that is easy to implement at an economical price to be used for daily needs. Therefore, a tool is designed to determine the quality of water that is sampled around the Tondo beach using the Fuzzy Logic method. This design was built using the Arduino module by combining four sensors, namely a pH sensor, a TDS sensor, a Turbidity sensor, and a temperature sensor. Water quality in this study was divided into three groups, namely drinking water (UM), washing water (UC), and unsuitable water (TL). The water quality benchmark value is known from combining the results of existing sensor readings, wherein sample 1, the value of water quality measured in the study is in the category not in accordance with the fuzzy value 10, in sample 2,the use of washing uses the fuzzy value of 45.68 and sample three is worth 26.4